A Case of Trapezium Avascular Necrosis Treated Conservatively. (25th May 2017) - Petsatodis, Evangelos; Ditsios, Konstantinos; Konstantinou, Panagiotis; Pinto, Iosafat; Kostretzis, Lazaros; Theodoroudis, Ioannis; Pilavaki, Mayia
Abstract : Introduction . Avascular necrosis (AVN) of the bones of the wrist most commonly involves the lunate followed by the proximal pole of the scaphoid and the capitate. Trapezium avascular necrosis is extremely rare with only two cases reported in the literature, both of which were treated surgically. In this article, we report a unique case of trapezium avascular necrosis treated conservatively. Case Presentation . A 38-year-old man complaining of a 4-month history of mild pain on the base of his right thumb. MRI scan was performed. The clinical presentation and the imaging findings indicated avascular osteonecrosis of the trapezium. The patient was treated with immobilization of the wrist joint for a period of six weeks. Three months later, the patient was free of symptoms and the MRI scan revealed a normal trapezium. Conclusion . AVN of trapezium is extremely rare. Our case shows that immobilization of an early stage avascular necrosis of the trapezium might be a treatment option.